Uncovering the anti-inflammatory mechanism of Jiang-Huang-Qing-Yan-Yin (JHQYY) in inflammatory bowel disease through network pharmacology, molecular docking, and cellular verification - Meng-Ru Liu; Yi-Ning Feng; Tao Sun; Bo Wang; Wei-Kang Yang; Wei Xue; Tian-Zhu Guan; Dan Xiong (Food & Medicine Homology, 2026)
Abstract Inflammation is a key driver of immune responses; however, its dysregulation can lead to chronic diseases such as inflammatory bowel disease (IBD). This study investigates the anti-inflammatory and antioxidant effects of Jiang-Huang-Qing-Yan-Yin (JHQYY), a multi-component herbal formula, using network pharmacology, molecular docking and cellular verification. Network pharmacology identified the main active ingredients: Tea polyphenols, vitamin E, vitamin C and caffeine, as well as their associated targets in JHQYY, revealing 44 compounds and 850 potential targets. Among these, 64 common targets were identified between JHQYY and IBD. Protein-protein interaction (PPI) network analysis highlighted key targets, including IL-6, TNF, ALB, and IL1B, which are critical in the pathogenesis of IBD. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses identified significant inflammatory and immune regulatory pathways, particularly the NF-κB and IL-17 signaling pathways. Molecular docking further confirmed that key active components, such as tea polyphenols and caffeine, exhibit strong interactions with inflammatory targets like TNF and ALB. JHQYY displayed strong antioxidant activity, with the aqueous extract showing superior ABTS radical scavenging capacity, while the alcohol extract demonstrated higher ferric-reducing antioxidant power (FRAP). Additionally, the cellular experiments demonstrated that JHQYY exhibited low cytotoxicity in RAW264.7 macrophages, significantly inhibited lactate dehydrogenase (LDH) release, and reduced the expression levels of pro-inflammatory cytokines (IL-1β, IL-6, TNF-α) induced by lipopolysaccharide (LPS). This research emphasizes that JHQYY has the potential to act as a natural anti-inflammatory substance and provides preliminary in vitro evidence supporting its anti-inflammatory potential relevant to IBD.